2010
DOI: 10.1007/s10600-010-9529-1
|View full text |Cite
|
Sign up to set email alerts
|

Amino-acid synthesis in aqueous media under ultrasonic irradiation

Abstract: The now-famous "Miller-Urey experiment" used a reduced mixture of gases to form basic organic molecules, such as amino acids. Since then, several methods have tried to reproduce the synthesis of amino acids under unusual conditions. All authors agree that the formation mechanisms of amino acids under such conditions might be of radical origin. If so, sonochemistry, known to enhance or to promote radical pathways, should be a powerful tool to access the synthesis of these compounds. We explored the feasibility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…It should be noted that Saladino et al have stated that the yield of the purine synthesis without a catalyst is only 1.7%. The formation of amino acids from formamide is the subject of a study published by Sedaghat et al Experimental works focused on the irradiation of formamide with UV light show that the molecule is photoactive. , …”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that Saladino et al have stated that the yield of the purine synthesis without a catalyst is only 1.7%. The formation of amino acids from formamide is the subject of a study published by Sedaghat et al Experimental works focused on the irradiation of formamide with UV light show that the molecule is photoactive. , …”
Section: Introductionmentioning
confidence: 99%
“… 30 These types of organic compounds were also found in our simulations starting with methane as the carbon source. A study that started with formamide in water 31 in an N 2 atmosphere as reactants resulted in the production of glycine, alanine, and aspartic acid. It was found that longer sonication times increased the concentration of amino acids but the concentration of formamide remained nearly constant, suggesting that it is also formed during the sonication.…”
Section: Discussionmentioning
confidence: 99%
“…(5). During the subsequent decade, Saladino, Di Mauro, and other authors developed complex synthetic pathways that not only account for the synthesis of nucleobases (6, 7) but also the formation of amino acids (8,9), sugars, nucleosides, nucleotides, simple oligonucleotide sequences, amino sugars, and carboxylic acids (10).…”
Section: Importance Of Formamide In Prebiotic Synthesismentioning
confidence: 99%